2014
DOI: 10.1620/tjem.232.1
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation Improves Exercise Capacity and Dyspnea in Air Pollution-Related Respiratory Disease

Abstract: Air pollution in Japan caused respiratory disease, such as chronic bronchitis and asthma, in many individuals in the 1960s. Although air pollution has decreased, many victims of air pollution-related respiratory disease are limited in their activities of daily living because of respiratory symptoms. The purpose of this study was to evaluate the efficacy of pulmonary rehabilitation in victims of air pollution-related chronic bronchitis or asthma. Subjects were enrolled in a 12-week (2-week inpatient followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 26 publications
1
40
0
1
Order By: Relevance
“…We found that at any particular point in time, the hazard of death among adult stroke patients who had any of the neuro-medical stroke complications was seven times higher than those who had no complications, after adjusting for potential confounders. This finding was in line with the studies done in Italy, 25 Taiwan, 26 Saudi Arabia, 1 this can be explained by the effect of stroke-related depressed immunity; depressed gag-reflex, and delayed mobilization of admitted patients. Early management of complications along with early mobilization and rehabilitation of patients, could significantly lower the incidence of complications, shortens the length of hospital stay and disability after the onset of stroke symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…We found that at any particular point in time, the hazard of death among adult stroke patients who had any of the neuro-medical stroke complications was seven times higher than those who had no complications, after adjusting for potential confounders. This finding was in line with the studies done in Italy, 25 Taiwan, 26 Saudi Arabia, 1 this can be explained by the effect of stroke-related depressed immunity; depressed gag-reflex, and delayed mobilization of admitted patients. Early management of complications along with early mobilization and rehabilitation of patients, could significantly lower the incidence of complications, shortens the length of hospital stay and disability after the onset of stroke symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Some stretching and chest expansion exercises can enlarge the thorax and increase the strength of the respiratory muscles. It is beneficial to increase lung capacity, lung ventilation, and oxygen utilization capacity to improve the working function of the lungs 194, 195…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study of patients with occupational-related respiratory disease, exercise capacity was significantly associated with a poorer psychological status 22 ) . We previously reported that officially acknowledged victims of pollution-related illness had low health-related quality of life and a high rate of depression 23 ) . Although we did not specifically study the relationship between mood and physical activity, we believe that they are likely to be closely associated in officially acknowledged victims of pollution-related illness.…”
Section: Discussionmentioning
confidence: 99%